Las capacidades coordinativas en los fundamentos técnicos del baloncesto de los alumnos del 8vo año de básica de la institución Emiliano Ortega Espinoza del cantón Catamayo período 2014- 2015 - Iñahuazo Moreno, Valeria Lizbeth (2016)
This research paper entitled coordinative CAPABILITIES IN BASKETBALL FUNDAMENTALS TECHNICAL STUDENTS 8TH YEAR OF BASIC INSTITUTION EMILIANO ORTEGA ESPINOZA CANTON CATAMAYO PERIOD 2014-2015; The problem was diagnosed How does coordination capacities in the Technical Fundamentals of Basketball? Its general objective: To identify the influence of coordination abilities in technical fundamentals of basketball; literature review revolves around variables coordinative capabilities and technical fundamentals of basketball; the type of research corresponds to a pre experimental design through the alternative proposal; to be an exploratory pre experimental study was conducted whose results allowed to observe the degree of impact of activities carried out in the proposal in relation to the stage in the pre and post test; the techniques were applied was the survey of 2 teachers of Physical Education and observation forms to the technical fundamentals of basketball and coordination capacities applied to 40 students. The results of the discussion were: once employed the exercises and games proposed 100% of students have achieved a significant improvement because they are in the process of achieving mastery of the technique of preparation, implementation and monitoring of the pass pectoris, baseball, protection dribbling, shooting hoops after displacement and the free kick. Regarding spatial capabilities temporo orientation, rhythm and balance, thanks to the implementation of this program students master the implementation phase of these capabilities. In conclusion, applied exercise program and specific games have influenced significantly in the technical fundamentals of basketball; it is recommended that periodically the implementation of the program for students strengthen coordination capacities in the technical fundamentals of basketball.